Engulfment and cell motility 1 (ELMO1) and apolipoprotein A1 (APOA1) as candidate genes for sickle cell nephropathy. (20th November 2020) - Saraf, Santosh L.; Zhang, Xu; Shah, Binal N.; Raslan, Rasha; Tayo, Bamidele O.; Lash, James P.; Franceschini, Nora; Gordeuk, Victor R.
Abstract: Sickle cell disease (SCD) and apolipoprotein L1 ( APOL1 ) G1/G2 variants increase chronic kidney disease (CKD) risk in African Americans by poorly understood mechanisms. We applied bioinformatics to identify new candidate genes associated with SCD‐related CKD. An interaction network demonstrated APOA1 connecting haemoglobin subunit β ( HBB ) and APOL1 with 36 other candidate genes. Gene expression revealed upregulation of engulfment and cell motility 1 ( ELMO1 ) and downregulation of APOA1 in the kidney cortex of SCD versus non‐SCD mice. Analysis of candidate genes identified ELMO1 rs10951509 to be associated with albuminuria and APOA1 rs11216132 with haemoglobinuria in patients with SCD. A bioinformatic approach highlights ELMO1 and APOA1 as potentially associated with SCD nephropathy.